Differences in Organizational Commitment between Male and Female Higher Secondary School Teachers - Sandhu, Dr. Dayal (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigated the organizational commitment with reference to gender amongst higher secondary school teachers. Descriptive Survey method is used for the research .Descriptive research design is used to accomplish the objective of the study. A sample of 110 higher secondary school teachers working in government and private schools were taken from Mathura district of Uttar Pradesh by random sampling technique. Mean, S.D., analysis of variance and t-test is used for analyzing the collecting data.